Treatment of Muscle-invasive and Metastatic Bladder Cancer: Update of the EAU Guidelines - Stenzl, Arnulf; Cowan, Nigel C.; De Santis, Maria; Kuczyk, Markus A.; Merseburger, Axel S.; Ribal, Maria José; Sherif, Amir; Witjes, J. Alfred (European urology, 2011)
New data regarding treatment of muscle-invasive and metastatic bladder cancer (MiM-BC) has emerged and led to an update of the European Association of Urology (EAU) guidelines for MiM-BC. To review the new EAU guidelines for MiM-BC with a specific focus on treatment. New literature published since the last update of the EAU guidelines in 2008 was obtained from Medline, the Cochrane Database of Systematic Reviews, and reference lists in publications and review articles and comprehensively screened by a group of urologists, oncologists, and a radiologist appointed by the EAU Guidelines Office. Previous recommendations based on the older literature on this subject were also taken into account. Levels of evidence (LEs) and grades of recommendations (GRs) were added based on a system modified from the Oxford Centre for Evidence-based Medicine Levels of Evidence. Current data demonstrate that neoadjuvant chemotherapy in conjunction with radical cystectomy (RC) is recommended in certain constellations of MiM-BC. RC remains the basic treatment of choice in localised invasive disease for both sexes. An attempt has been made to define the extent of surgery under standard conditions in both sexes. An orthotopic bladder substitute should be offered to both male and female patients lacking any contraindications, such as no tumour at the level of urethral dissection. In contrast to neoadjuvant chemotherapy, current advice recommends the use of adjuvant chemotherapy only within clinical trials. Multimodality bladder-preserving treatment in localised disease is currently regarded only as an alternative in selected, well-informed, and compliant patients for whom cystectomy is not considered for medical or personal reasons. In metastatic disease, the first-line treatment for patients fit enough to sustain cisplatin remains cisplatin-containing combination chemotherapy. With the advent of vinflunine, second-line chemotherapy has become available. In the treatment of localised invasive bladder cancer (BCa), the standard treatment remains radical surgical removal of the bladder within standard limits, including as-yet-unspecified regional lymph nodes. However, the addition of neoadjuvant chemotherapy must be considered for certain specific patient groups. A new drug for second-line chemotherapy (vinflunine) in metastatic disease has been approved and is recommended. The European Association of Urology guidelines group on muscle-invasive and metastatic bladder cancer (MiM-BC) have updated the guidelines on MiM-BC. Data strongly support the use of neoadjuvant chemotherapy, regardless of any further treatment selected. Radical cystectomy is still the standard of care for localised muscle-invasive bladder cancer. Accurate patient selection, definition of surgical techniques, postoperative morbidity and careful postoperative follow-up are defined.